Base‐Dependent Stereodivergent Intramolecular Aza‐Michael Reaction: Asymmetric Synthesis of 1, 3‐Disubstituted Isoindolines. Issue 35 (12th July 2013) - Fustero, Santos; Herrera, Lidia; Lázaro, Ruben; Rodríguez, Elsa; Maestro, Miguel A.; Mateu, Natalia; Barrio, Pablo
Abstract The nucleophilic addition (AN) / intramolecular aza‐Michael reaction (IMAMR) process on Ellman's tert‐butylsulfinyl imines, bearing a Michael acceptor in the ortho position, is studied. This reaction affords 1, 3‐disubstituted isoindolines with a wide range of substituents in good yields and diastereoselectivities. Interestingly, careful choice of the base for the aza‐Michael step allows either the cis or the trans diastereoisomers to be exclusively obtained. This stereodivergent cyclization has enabled the synthesis of C2‐symmetric bisacetate‐substituted isoindolines. In addition, bisacetate isoindolines bearing two well‐differentiated ester moieties are also noteworthy because they may allow for the orthogonal synthesis of β, β′‐dipeptides using a single nitrogen atom as a linchpin.